Keragaman warna bunga m1 tanaman aster (Callistephus chinensis) Hasil induksi mutasi iradiasi sinar gamma - Yanuar Rizqiani; Florentina Kusmiyati; Syaiful Anwar (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
The aims of research was to determine the effect of gamma ray on the flower colour of Daisies. The research design was completely randomized design with five replicates. The irradiation treatment of gamma ray were 0 Gy, 5 Gy, 10 Gy, 15 Gy, 20 Gy. Parameters observed were stalk length, time of flowering, number of flowers, flower diameter, and flower colour. The collected data were analyzed by analysis of variance (ANOVA) and continued by Least Significance Different (LSD) of 5% level. The result showed that irradiation of gamma ray did not affected stalk length, number of flowers, and time of flowering. The gamma ray irradiation had a significant effect on flower diameter. Gamma ray irradiation significantly decreased the diameter of flower. The flower colour at doses 0 Gy (control) was purple. Colour flower was varied from dark purple to pink at irradiation 10 Gy and 15 Gy. Keywords: Callistephus chinensis, mutation, irradiation, colour of flower.